PENERAPAN PERMAINAN BOLA POMPOM DALAM MENINGKATKAN KECERDASAN VISUAL PADA ANAK USIA DINI DI KB AL-GHIFARI - Nadia Fauziah; Heni Nafiqoh (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2021)
Children are a gift that is unique in themselves often called the golden age, therefore it needs good assistance from parents or the environment so that children's development develops well, such as honing children in visual intelligence. The purpose of this article is to determine the activities of early childhood in improving visual intelligence through pompom ball games in one of the PAUD institutions, namely the KB Al-Ghifari 2019-2020 academic year. This study uses a qualitative descriptive method by collecting information about problems that exist in the environment of children and schools, so the researchers describe how the learning process and focus on students, the data collection technique was done by observing interviews and documentation. The subjects in the study consisted of school principals, teachers, and 17 children consisting of 10 girls and 7 boys. Enhancing research data on visual intelligence will be analyzed using an interactive analysis model, namely, by collecting data, data reduction, data presentation, and the final result will be clearly and validly described.   The results of the analysis of the data on the development of children’s visual intelligence can be concluded from the first meeting to the next meeting with the application of pompom ball games in improving children’s visual intelligence in group A aged 4-5 years in KB Al-Ghifari.Anak merupakan  anugrah  yang mempunyai  keunikan  dalam dirinya  sering  disebut dengan  masa  golden age  oleh sebab itu perlu pendampingan  yang baik dari orang tua atau  ligkungan agar  perkembangan anak  berkembang secara  baik, seperti mengasah  anak dalam  kecerdasan visual.  Adapun tujuan dalam artikel untuk mengetahui aktivitas anak usia dini dalam  meningkatkan  kecerdasan visual melalui permainan  bola pompom  di  salah satu  lembaga  PAUD yaitu  KB Al-Ghifari  tahun ajaran 2019-2020.  Penelitian ini menggunakan metode deskriptif  kualitatif  dengan mengumpulkan  informasi  tentang permasalahan yang ada dalam lingkungan anak dan sekolah. Maka peneliti  mendeskriptifkan  bagaimana proses  pembelajarannya dan fokus  ke peserta didik.  Teknik  pengumpulan data  dilakukan  dengan observasi, wawancara dan dokumentasi.Subjek dalam  penelitian  terdiri dari  kepala sekolah,  guru dan  anak berjumlah 17 anak  yang terdiri dari 10 perempuan dan 7 laki-laki .  Data  penelitian peningkatkan  pada  kecerdasan visual  akan di analisis  dengan menggunakan  model  analisis interaktif , yaitu dengan cara pengumpulan data,  reduksi data, penyajian data serta hasil akhir akan dideskriftipkan  dengan jelas  dan  valid.  Hasil analisis dari  data  perkembangan kecerdasan  visual  anak dapat disimpulkan  dari pertemuan pertama ke pertemuan selanjutnya dengan  penerapan permainan  bola pompom dalam meningkatkan kecerdasan visual anak pada kelompok A usia 4-5 tahun di KB Al-Ghifari.